The Scoping Review of Strengths and Weaknesses in Applying Green Leadership in Schools - Shodikin, Rifan; Sudarsyah, Asep; Komariah, Aan; Ruhimat, Mochammad Devi Cahya; Jiewei, Wu (PAEDAGOGIA, 2025)
This research aims to identify the strengths and weaknesses of green leadership implementation in school environments as a response to the increasingly pressing climate crisis today. Using a qualitative approach with a scoping review method, this study successfully analyzed eight selected scientific articles obtained from the Scopus and Google Scholar databases based on strict inclusion and exclusion criteria. The analysis results indicate that green leadership practices significantly positively impact various aspects of education, such as improving student academic achievement, teacher collaboration, equalizing access to education, and strengthening a culture of environmental care. However, this study also reveals challenges in measuring effectiveness due to the lack of comprehensive implementation guidelines. Therefore, the development of a systematic sustainable leadership strategy is needed to prevent managerial chaos and support a consistent vision of sustainability in the school environment